Kinetic analysis of particle-size based complex kinetic processes - Svoboda, Roman (Elsevier Science BV, 2020)
Complex kinetic data arbitrarily created by measuring (calorimetrically) crystallization of mixed selenium powders with different defined particle sizes were evaluated by the three standard approaches to complex kinetic analysis. Performance of the three tested approaches was tested by comparison with the kinetic results obtained for the separate powder fractions. The additivity of the kinetic signals was verified. Single-process methods of kinetic analysis provided qualitative and quantitative information about the temperature dependence of activation energy E and estimation of the ratio between intensities of the involved sub-processes I-1/I-2. Mathematic deconvolution approach well reflected the correct model-free and model-based kinetics for the partial overlaps. However, it required iterative processing and additional supplemental information about the nature of the sub-processes in case of the evaluation of fully overlapping data. Kinetic deconvolution based on single-curve non-linear optimization utilizing the fixed E values obtained independently provided very good results for both, partial and full overlaps.
Kinetická analýza komplexních kinetických procesů ovlivněných velikostí částic
Keywords: complex kinetic analysis; particle size; DSC; selenium glass; deconvolution; komplexní kinetická analýza; velikost částic; DSC; amorfní Se; dekonvoluce